Sistem Monitoring Ketinggian Air Tangki Tanaman Hidroponik Berbasis Website - Zhou, Adi Putera; Fatah, Dwi; Barri, Daffa Ariesta Fathul; Irwan, Irwan; Fujiyanti, Linda (Jurnal Inovasi Teknologi Terapan, 2023)
The application of hydroponics in the agricultural sector is very effective for maximizing limited land in urban environments (urban farming). This one farming system requires extra supervision to get quality crop yields. One aspect to which farmers must pay attention is monitoring the water level in the tank so that the water discharge needed by hydroponic plants is properly fulfilled. In order to provide convenience to farmers in carrying out this monitoring, this research is designed to monitor the water level of the tank based on a website. The use of ultrasonic sensors in this study is as a distance sensor. Sensor data that has been obtained from the ultrasonic sensor is then processed by the Arduino Uno and sent to the NodeMCU ESP8266 to be sent to a database that is connected via the internet network so that it can be used by users anywhere and anytime through websites connected to the internet. The level of accuracy of the data on the website is 100% according to the reading results from the Arduino IDE application and a ruler as a comparison measure.